Experimental study on the synergistic effect of nanogel and low salinity water on enhanced oil recovery for carbonate reservoirs. (1st April 2020) - Han, Pu; Geng, Jiaming; Ding, Haifeng; Zhang, Ye; Bai, Baojun
Abstract: Recent researches show the abilities of nano-sized crosslinked polymeric particles (nanogels) and low salinity water (LSW) in recovering residual oil. However, the synergy between nanogels and LSW are not clear, especially in porous media. Herein, we synthesized poly(2-acrylamido-2methylpropane sulfonic acid, sodium salt) (PAMPS-Na) nanogels and studied their size and zeta potential in formation water (FW), seawater (SW), and LSW. The combination of PAMPS-Na nanogels and LSW effectively altered the wettability of limestone surface from strong oil-wet to intermediate-wet. The adsorption of PAMPS-Na nanogels at the oil-water interface rendered ultra-low interfacial tensions between crude oil and salines. For the kinetic adsorption in limestone cores, the PAMPS-Na nanogels displayed a solute-like reversible adsorption behavior in FW and SW whereas an irreversible adsorption behavior in LSW. The limestone flooded with LSW and PAMPS-Na nanogels achieved a 62.4% ultimate oil recovery. These results suggest that the synergistic effect between LSW and nanogels offers a promising platform for enhancing oil recovery.